Peran Media Pembelajaran Berbasis Teknologi dalam Meningkatkan Minat Baca Siswa SD - Yeni Nuraeni; Serawati Serawati; Siti Alya Solihats; Fathiya Rachma Kamilla; Lutfinurul Karomah; Sri Surya Junari (Lembag, 2025)
This study aims to analyze the role of technology-based learning media in increasing the reading interest of elementary school (SD) students in the digital era. Using a qualitative approach, data was collected through in-depth interviews, observations, and document analysis in several schools that have implemented technology in the learning process. So that data collection techniques are obtained from the results of observations, interviews, and literature studies. The results showed that the use of media such as e-books, educational apps, and interactive videos significantly increased students' interest in reading, with students showing higher enthusiasm for the reading material presented interactively. In addition, support from teachers and parents is very important in creating a conducive learning environment. These findings confirm that the integration of technology in learning not only makes the learning process more interesting, but also contributes to the improvement of literacy elementary school students. This research is expected to provide insight for educators and policymakers in designing more effective learning strategies.